The Use of Problem-based Learning Method Assisted with Story Mapping to Improve Reading Comprehension - Mutiara Oktarina; Rofiqoh Rofiqoh; Sriati Usman; Wahyudin Wahyudin (Universitas Cokroaminoto Palopo, 2024)
This research aims to prove whether the use of problem-based learning method assisted with story mapping can improve the reading comprehension of the eighth grade students of SMP Negeri 4 Palu. The researcher applied a quasi-experimental research design. The sample was selected through a purposive sampling technique, consisting of experimental and control groups with a total sample of 60 students. The data were collected through a reading test consisting of the pre-test and post-test. The collected data was analyzed statistically using SPSS 22. By using a 0.05 level of significance with the degree of freedom (58), the researcher found the sig. value was smaller than the chosen alpha level (0.001<0.05). It reveals that the hypothesis is accepted or the use of Problem-based Learning method assisted with Story Mapping can improve the reading comprehension of the eighth grade students of SMP Negeri 4 Palu. The implication of the findings were the use of PBL method assisted with story mapping can train students’ thinking and collaborative skills, thus making them more actively participate in the discussion and engage in critical and creative thinking